A modification of inclusion of a zero of a function using interval method - Abd Rahmin, Nor Aliza; Monsi, Mansor; Abu Hassan, Malik; Ismail, Fudziah (Universiti Putra Malaysia Press, 2009)
Interval method is used for the inclusion of a zero of a function. The Ehrman (EHR) method considers the Newton’s iteration in finding the root of a function. This method is modified by using the mid point in the procedure and improved method has a faster convergence rate and less processing time. In this paper, the convergence analysis and the numerical results are shown.